She’s Really Kind and Hella Weird! ─ The Use of Intensifiers among Teens: A Sociolinguistic Analysis - Calista Putri; Hairus Salikin; Dewianti Khazanah (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2020)
This study aims to reveal language variation of the use of intensifiers that occurs between male and female teens. This study will also examine the effects of gender through the use of adjectives intensification. Seeing that society have stereotype towards male and female, it is being one of problems that cause the differences in their language. To answer this problem, qualitative and quantitative approaches are undertaken. All participants are asked to share stories through free writing section. A later interview process is accomplished to clarify their further reasons of their intensifiers. The results show that there are significant differences of intensifiers used by males and females such as intensifiers amount, adjective types, degree, positive-negative evaluation, emotional value, intensifiers choices, and the use of double and taboo intensifiers. These differences are caused by several reasons with gender related. It has connection with power, politeness, expressions, emotion, society compulsion, and others.